FAKTOR YANG MEMPENGARUHI PENGOLAHAN SAMPAH RUMAH TANGGA DI RW 03 DESA TARAI BANGUN KAB KAMPAR - Zurni Seprina; Eliza Fitria; Betty Nia Rulen; Ratna Juwita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Waste is basically solid material left over from human activities or natural processes. The higher the population and various activities, the more the generation and variety of waste produced, this type of research is quantitative correlational with cross sectional method. Where the independent variable and the dependent variable are examined at the same time. The population in this study were all households in RW 03 Tarai Bangun Village and by calculating the sample using the slovin formula, a total sample of 66 respondents was obtained. The research was conducted at RW 03 Tarai Bangun Village, Kampar Regency. Time of Research The research was carried out in September 2021. The data analysis tests carried out were univariate analysis and bivariate analysis using the Chi Square statistical test. The results showed that there was no effect of education (P value 1.000), knowledge (P value 0.420), attitude (P value 0.420) of the community in processing household waste in RW 03 Tarai Bangun Village in 2021.Keywords: Garbage; Knowledge; Attitude; Education.